Preparation of Al2O3/MgO Nano-Composite Particles for Bio-Applications - Hayder Sallal; Alla Abdul-Hameed; Farhad. Othman (Engineering and Technology Journal, 2020)
This study describes the preparation and study of the properties of Nano composite particles prepared in a sol-gel method which consists of two materials (Αl2Ο3-MgΟ). The powder was evaluated by x-ray diffraction analysis, scanning electron microscopy analysis (SEM), particle size analysis, and energy dispersive x-ray analysis (EDX) and antibacterial test. The evaluation results of the nanocomposite particles shows a good distribution of the chemical composition between aluminum oxide and magnesium oxide, smoothness in particles size where it reached to (54.9, 59.8) nm at calcination in (550 0C and 850 0C) respectively, formation of different shapes of nanoparticles and different phases of the Αl2Ο3 particles (kappa and gamma) and nanopowder have well antibacterial action, Therefore, this reflects the efficiency of the proposed method to manufacture the nanocomposite powder and the possibility of using this powder as a strengthening material for the composite materials and using these composite materials in bio applications, especially in the fabrication of artificial limbs.